Deleterious Effects of Cold Air Inhalation on Coronary Physiological Indices in Patients With Obstructive Coronary Artery Disease. Issue 14 (17th July 2018) - Williams, Rupert P.; Asrress, Kaleab N.; Lumley, Matthew; Arri, Satpal; Patterson, Tiffany; Ellis, Howard; Manou‐Stathopoulou, Vasiliki; Macfarlane, Catherine; Chandran, Shruthi; Moschonas, Kostantinos; Oakeshott, Pippa; Lockie, Timothy; et al.
Abstract : Background: Cold air inhalation during exercise increases cardiac mortality, but the pathophysiology is unclear. During cold and exercise, dual‐sensor intracoronary wires measured coronary microvascular resistance (MVR) and blood flow velocity (CBF), and cardiac magnetic resonance measured subendocardial perfusion. Methods and Results: Forty‐two patients (62±9 years) undergoing cardiac catheterization, 32 with obstructive coronary stenoses and 10 without, performed either (1) 5 minutes of cold air inhalation (5°F) or (2) two 5‐minute supine‐cycling periods: 1 at room temperature and 1 during cold air inhalation (5°F) (randomized order). We compared rest and peak stress MVR, CBF, and subendocardial perfusion measurements. In patients with unobstructed coronary arteries (n=10), cold air inhalation at rest decreased MVR by 6% ( P =0.41), increasing CBF by 20% ( P <0.01). However, in patients with obstructive stenoses (n=10), cold air inhalation at rest increased MVR by 17% ( P <0.01), reducing CBF by 3% ( P =0.85). Consequently, in patients with obstructive stenoses undergoing the cardiac magnetic resonance protocol (n=10), cold air inhalation reduced subendocardial perfusion ( P <0.05). Only patients with obstructive stenoses performed this protocol (n=12). Cycling at room temperature decreased MVR by 29% ( P <0.001) and increased CBF by 61% ( P <0.001). However, cold air inhalation during cycling blunted these adaptations in MVR ( P =0.12) and CBF ( P <0.05), an effect attributable to defective early diastolic CBF acceleration ( P <0.05) and associated with greater ST‐segment depression ( P <0.05). Conclusions: In patients with obstructive coronary stenoses, cold air inhalation causes deleterious changes in MVR and CBF. These diminish or abolish the normal adaptations during exertion that ordinarily match myocardial blood supply to demand.